2005
DOI: 10.1038/sj.cdd.4401799
|View full text |Cite
|
Sign up to set email alerts
|

BMP-4 induces a Smad-dependent apoptotic cell death of mouse embryonic stem cell-derived neural precursors

Abstract: Embryonic ectoderm is fated to become either neural or epidermal, depending on patterning processes that occur before and during gastrulation. It has been stated that epidermal commitment proceeds from a bone morphogenetic protein-4 (BMP-4)-dependent inhibition of dorsal ectoderm neuralization. We recently demonstrated that murine embryonic stem (ES) cells treated with BMP-4 undergo effective keratinocyte commitment and epidermogenesis. Focusing on the precise role of BMP-4 in the early choice between neural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 41 publications
5
69
1
4
Order By: Relevance
“…The latter instead function by counteracting the apoptosis induced by BMP4. Indeed, it was previously demonstrated that low doses of BMP4 are able to induce the apoptosis of ESCs, 29 and we demonstrated that suppression of the miRs of the 23a and 23b clusters leads to massive apoptosis of differentiating cells. Therefore, the results support the possibility that the accumulation of these miRs is intended to protect ESCs from an inappropriate apoptosis induced by BMP4.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The latter instead function by counteracting the apoptosis induced by BMP4. Indeed, it was previously demonstrated that low doses of BMP4 are able to induce the apoptosis of ESCs, 29 and we demonstrated that suppression of the miRs of the 23a and 23b clusters leads to massive apoptosis of differentiating cells. Therefore, the results support the possibility that the accumulation of these miRs is intended to protect ESCs from an inappropriate apoptosis induced by BMP4.…”
Section: Discussionsupporting
confidence: 53%
“…2 In contrast, it was also observed that low doses of BMP4 induce apoptosis during epidermal differentiation of ESCs. 29 We reasoned that suppression of miR-clusters can result in an enhancement of the endogenous signaling that mimics the exposure of the cells to low doses of BMP4. Thus, we treated ESCs with different doses of BMP4 and the onset of apoptotic phenotype was analyzed by measuring the level of cleaved caspase-3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, no change in expression of ectodermal markers, including inhibin ␤ B, Fgf5, and neurofilament-200 (N-200;Roche et al, 2005; Fig. 6A,B), or in the expression of the neuronal precursor cell marker, Sox1 (Gambaro et al, 2006) was observed in Gcn5 Ϫ/Ϫ EBs. However, the timing of expression of some mesodermal marker genes was altered in the mutant EBs.…”
Section: Gcn5 Null Es Cells Differentiate Into Ectoderm Mesoderm Anmentioning
confidence: 92%
“…38,39 Thus the free virus group may perform similar to the lyophilization group in a limited medium environment. Because reducing the infection volume is impractical for in vivo delivery, we localized adenovirus on the material surface by lyophilizing with appropriate excipients that enhanced virus adhesion.…”
Section: Discussionmentioning
confidence: 99%